Role of Epigenetic Modifications in Inhibitory Immune Checkpoints in Cancer Development and Progression - Saleh, Reem; Toor, Salman M.; Sasidharan Nair, Varun; Elkord, Eyad (Frontiers in Immunology, 2020)
A balance between co-inhibitory and co-stimulatory signals in the tumor microenvironment (TME) is critical to suppress tumor development and progression, primarily via maintaining effective immunosurveillance. Aberrant expressions of immune checkpoints (ICs), including programmed cell death protein 1 (PD-1), cytotoxic T-lymphocyte-associated protein 4 (CTLA-4), T cell immunoglobulin and mucin-domain containing-3 (TIM-3), lymphocyte-activation gene 3 (LAG-3) and T cell immunoreceptor with Ig and ITIM domains (TIGIT), can create an immune-subversive environment, which helps tumor cells to evade immune destruction. Recent studies showed that epigenetic modifications play critical roles in regulating the expression of ICs and their ligands in the TME. Reports showed that the promoter regions of genes encoding ICs/ligands can undergo inherent epigenetic alterations, such as DNA methylation and histone modifications (acetylation and methylation). These epigenetic aberrations can significantly contribute to the transcriptomic upregulation of ICs and their ligands. Epigenetic therapeutics, including DNA methyltransferases and histone deacetylase inhibitors, can be used to revert these epigenetic anomalies acquired during the progression of disease. These discoveries have established a promising therapeutic modality utilizing the combination of epigenetic and immunotherapeutic agents to restore the physiological epigenetic profile and to re-establish potent host immunosurveillance mechanisms. In this review, we highlight the role of epigenetic modifications on the upregulation of ICs, focusing on tumor development and progression. We discuss therapeutic approaches of epigenetic modifiers, including clinical trials in various cancer settings and their impact on current and future anti-cancer therapies.